2003
DOI: 10.1086/345476
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mortality Associated with Methicillin‐Resistant and Methicillin‐SusceptibleStaphylococcus aureusBacteremia: A Meta‐analysis

Abstract: A meta-analysis was performed to summarize the impact of methicillin-resistance on mortality in Staphylococcus aureus bacteremia. A search of the MEDLINE database for studies published during the period of 1 January 1980 through 31 December 2000 and a bibliographic review identified English-language studies of S. aureus bacteremia. Studies were included if they contained the numbers of and mortality rates for patients with methicillin-resistant S. aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
1,003
14
48

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,767 publications
(1,105 citation statements)
references
References 52 publications
40
1,003
14
48
Order By: Relevance
“…Studies especially focusing on morbidity differences are limited, while the impact of methicillin resistance on mortality has been extensively studied for SA bacteremia and several-but not all-studies, including two meta-analyses, have reported a real effect. 27,[46][47][48][49] A main reason for this apparent disagreement may be a case-mix effect due to the variety of SA infections included in our study groups and this attenuation phenomenon has also been noted elsewhere. 18 Another reason may be the significantly higher percentage of bloodstream infections in the MSSA group.…”
Section: Outcome Analysismentioning
confidence: 89%
“…Studies especially focusing on morbidity differences are limited, while the impact of methicillin resistance on mortality has been extensively studied for SA bacteremia and several-but not all-studies, including two meta-analyses, have reported a real effect. 27,[46][47][48][49] A main reason for this apparent disagreement may be a case-mix effect due to the variety of SA infections included in our study groups and this attenuation phenomenon has also been noted elsewhere. 18 Another reason may be the significantly higher percentage of bloodstream infections in the MSSA group.…”
Section: Outcome Analysismentioning
confidence: 89%
“…Patients with MRSA bacteremia have been shown to have a higher mortality risk and higher healthcare costs than those with MSSA infections, and a meta-analysis of 31 studies of patients with S. aureus bloodstream infections demonstrated a significant increase in mortality among patients with MRSA vs. MSSA bacteremia. [18][19][20] Outcomes when comparing MRSA and MSSA in VAP are slightly more variable. A higher rate of mortality has been reported in patients with pneumonia caused by MRSA vs. MSSA, but others found no difference after controlling for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los factores relacionados con el tratamiento, se han identificado la resistencia a la meticilina (55,63,64), el retraso en el diagnóstico (52), la persistencia de cuerpos extraños (65,66) o focos no removibles (52,56), la persistencia de la fiebre después de 72 horas (16,56) y el retraso en la administración del antibiótico apropiado por más de 44 horas (63), como factores que predicen una mayor probabilidad de fracaso terapéutico, siembras metastásicas y recurrencia. La mayoría de estos estudios corresponden a estudios de cohorte, con tiempos variables de seguimiento.…”
Section: Factores De Riesgo Y Pronósticosunclassified
“…Debido a la aparición de cepas de S. aureus con resistencia intermedia a la vancomicina o SARV, se han introducido nuevos antibióticos, entre los que se encuentran linezolid (familia oxazolidinona), quinupristin/dalfopristin (familia estreptogramina, no disponible en Colombia), daptomicina (lipopéptido cíclico, no disponible en Colombia), entre otros (1,13,15,33,-34,54,63,64,71,73); no hay que olvidar otros antibióticos como trimetoprim-sulfametoxazol, clindamicina, rifampicina, fluoroquinolonas, teniendo en mente que el gen MecA puede conferir resistencia variable a uno o varios de estos antibióticos (15,18,54,63,64,71,74). Cabe recordar que la vancomicina no se considera tan efectiva como los beta-lactámicos, por lo que siempre que sea posible se debe preferir el uso de penicilinas antiestafilocóccicas antes que de vancomicina (55,75) (cuadro 3).…”
Section: Evidencia De Compromiso Endocárdicounclassified